2005
DOI: 10.1212/01.wnl.0000178989.87072.11
|View full text |Cite
|
Sign up to set email alerts
|

Serum cholesterol and risk of Alzheimer disease

Abstract: The data do not support an association between serum total cholesterol or high density lipoprotein in late life and subsequent risk of dementia or Alzheimer disease (AD). The increased risk of AD with APOE-epsilon4 is probably not mediated by serum total cholesterol levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
111
4
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 46 publications
(66 reference statements)
9
111
4
2
Order By: Relevance
“…Similar results were reported recently in a study that found no association between cholesterol or HDL-C and risk of dementia in a community-based study of cognitively intact elderly subjects. 26 In conclusion, this large-scale cognition study embedded in a clinical trial revealed that, over an average 3.2-year period, the presence of the apolipoprotein E 4 isoform was associated with greater decline in memory performance without apparently affecting attention or processing ability. The apolipoprotein E4 isoform was linked also to morepronounced deterioration in indices of ADLs and IADLs.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Similar results were reported recently in a study that found no association between cholesterol or HDL-C and risk of dementia in a community-based study of cognitively intact elderly subjects. 26 In conclusion, this large-scale cognition study embedded in a clinical trial revealed that, over an average 3.2-year period, the presence of the apolipoprotein E 4 isoform was associated with greater decline in memory performance without apparently affecting attention or processing ability. The apolipoprotein E4 isoform was linked also to morepronounced deterioration in indices of ADLs and IADLs.…”
Section: Discussionmentioning
confidence: 70%
“…22 The nature of the association between lipid and lipoprotein levels and cognitive impairment is largely unknown, with conflicting results being reported. [23][24][25][26] Recently, low highdensity lipoprotein cholesterol (HDL-C) levels have been linked to poorer cognitive function, independent of an effect on cardiovascular disease in the oldest old, 23 whereas no association between total plasma cholesterol or HDL-C and risk of Alzheimer's disease was observed in another study. 26 The Prospective Study of Pravastatin in the Elderly at Risk (PROSPER) was a trial of statin use for the prevention of cardiovascular and cerebrovascular disease in 5,804 men and women aged 70 to 82.…”
mentioning
confidence: 99%
“…Based on previous studies, HDL-C does not seem to associate with dementia or AD (Li et al 2005;Reitz et al 2010;Arntzen et al 2011) albeit the association is Total cholesterol, HDL cholesterol, systolic blood pressure, body mass index, apolipoprotein A-I, apolipoprotein B, and apolipoprotein B/A ratio were log-transformed before multivariate analysis a Model is not adjusted for total cholesterol apo A-I apolipoprotein A-I, HDL-C high density lipoprotein cholesterol, apo B apolipoprotein B, apo B/A ratio ratio between apo B and apo A-I seen in cross-sectional studies (Merched et al 2000). These findings are in line with our results where death is considered as a competing risk for dementia and AD, and statistically significant association is seen in CIF but not in Cox regression model between HDL-C and AD.…”
Section: Discussionmentioning
confidence: 91%
“…Higher total serum cholesterol (TC) in midlife is associated with higher risk of AD (Kivipelto et al 2001;Li et al 2005;Solomon et al 2007) but the association of TC and dementia risk is reversed in later life (Mielke et al 2005). Low levels of high density lipoprotein cholesterol (HDL-C) also associate with adverse cerebral white matter changes (Gouw et al 2008;Crisby et al 2010), but no clear association of HDL with the risk of dementia or AD has been found in prospective studies (Li et al 2005;Reitz et al 2005;Reitz et al 2010;Arntzen et al 2011). Apolipoprotein A-I (apo A-I) is the major surface protein of HDL-C, which is associated with lower risk for cardiovascular diseases (CVD).…”
Section: Introductionmentioning
confidence: 99%
“…However, several recent studies have not supported the idea of a link between cholesterol levels and risk of Alzheimer 654,655,656 disease.…”
Section: Genewatch Uk January 2006mentioning
confidence: 98%